2022
DOI: 10.1108/jrim-04-2021-0114
|View full text |Cite
|
Sign up to set email alerts
|

Creating immersive and parasocial live shopping experience for viewers: the role of streamers' interactional communication style

Abstract: PurposeLive streaming commerce has grown rapidly in recent years. Although the way streamers communicate with viewers is the key to influencing users' purchase behaviors, little is known about the influence of streamers' communication style on purchase intention. Drawing on parasocial interaction theory and flow theory, this study examines the influence of streamers' interaction orientation on viewers' immersion and parasocial interactions, and its effect on viewers' purchase intentions. The moderating effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 64 publications
4
39
0
1
Order By: Relevance
“…Previous research has highlighted the role of celebrity engagement in customer engagement (Wang and Hu, 2021; Wang, 2021), firms’ brand value (Knoll and Matthes, 2017; Zimand Sheiner et al , 2021) and sales performance (Chen et al , 2021; Liao et al , 2022). Amos et al (2008) found celebrities’ trustworthiness, expertise and attractiveness as three most important factors affecting customer purchase intention, brand attitude and ad attitude.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has highlighted the role of celebrity engagement in customer engagement (Wang and Hu, 2021; Wang, 2021), firms’ brand value (Knoll and Matthes, 2017; Zimand Sheiner et al , 2021) and sales performance (Chen et al , 2021; Liao et al , 2022). Amos et al (2008) found celebrities’ trustworthiness, expertise and attractiveness as three most important factors affecting customer purchase intention, brand attitude and ad attitude.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Chang et al (2011) found that the characteristics of the retail environment influence impulse buying through consumers’ positive emotional responses. Interactivity and entertainment atmospheres, such as anchors’ interaction orientation, will have a positive effect on viewers’ immersion ( Liao et al, 2022 ), causing people to lose track of time, disregard their surroundings, and experience intense pleasure and arousal ( Van Noort et al, 2012 ). Hence, consumers are readily affected by the persuasion of anchors, leading to more impulsive buying behavior.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…According to the Table 4, majority of the articles employed multidimensional flow in their framework. Only five articles (Article 2, 4, 21, 22, and 24) applied unidimensional flow in their research (Baker et al, 2019;Herrando et al, 2017;Huang, 2016;Liao et al, 2022;Xie et al, 2020). The article number listed in Table 4 was referenced to the publication title in Appendix A1.…”
Section: Dimensions Of Flowmentioning
confidence: 99%